Cytokine–Adipokine Profile And Microcirculatory Parameters As Interrelated Determinants Of Subclinical Polyneuropathy - Kodirova Nargizakhon Umarovna; Djuraeva Aziza Shakhzadeevna (International Journal of Medical Sciences And Clinical Research, 2025)
Background. Subclinical peripheral polyneuropathy (PPN) frequently develops in prediabetes and obesity but often remains undetected. The contribution of cytokine–adipokine imbalance and microcirculatory dysfunction to early nerve injury requires clarification. Objective. To assess how cytokine–adipokine markers and microcirculatory parameters relate to subclinical PPN and to determine their independent predictive value. Materials and Methods. A cross-sectional study included 120 adults: 80 with prediabetes and obesity and 40 healthy controls. Subclinical PPN was defined by normal neurological scores combined with ≥2 abnormal tests (QST deviations, reduced IENFD, or decreased sensory conduction velocity). Serum leptin, adiponectin, IL-6, TNF-α, hsCRP, and the leptin-to-adiponectin ratio (L/A-ratio) were measured. Microcirculation was evaluated by laser Doppler flowmetry and nailfold capillaroscopy. Multivariable regression and ROC analysis were applied. Results. Subclinical PPN was found in 41.3% of the main group. Affected individuals had significantly higher L/A-ratio and inflammatory cytokines, along with reduced endothelial oscillations, post-occlusive hyperemia, and capillary density. L/A-ratio, IL-6, and endothelial oscillation amplitude were independently associated with PPN, and their combination showed high accuracy (AUC 0.88). Conclusions. Subclinical PPN in prediabetes with obesity is strongly linked to adipokine imbalance, systemic inflammation, and microvascular dysfunction. Combined biochemical and microcirculatory markers may improve early risk identification and warrant longitudinal validation.